Calcium hydroxide liners: a literature review - Arandi NZ (Dove Medical Press, 2017)
Naji Ziad Arandi Faculty of Dentistry, The Arab American University, Jenin, Palestine Objective: This review integrates the literature on cavity liners and current concepts of pulp protection with the aim of establishing a better understanding of the role of calcium hydroxide as a cavity liner.Materials and methods: A search was conducted through PubMed, MEDLINE, and Ovid for articles with the criteria for the following terms: cavity liners and bases, pulp protection, and calcium hydroxide liners. No specific inclusion or exclusion criteria were applied as to what articles would be included in this review. It was hoped that the extent of the literature reviewed would be as comprehensive as possible.Conclusion: This review underlines the fact that calcium hydroxide liners should only be used in the deepest spots in the cavity where the remaining dentine thickness is ≤0.5 mm. A protective layer of resin-modified glass ionomer should always follow the application of calcium hydroxide liners. Keywords: liners, calcium hydroxide, pulp protection, pulp therapy, bases